Implementation of Welfare Guarantees for Persons with Disabilities at The Intellectual Disability Social Service Institution of "Raharjo" Sragen - Aditya Nugrahanto; Marisa Kurnianingsih (Proceeding International Conference Restructuring and Transforming Law, 2025)
This article was written to determine the implementation of welfare guarantees at Intellectual Disability Social Service Institution of "Raharjo" Sragen. This research was written using the juridical-empirical method with an observation, interview and document research approach as a means of supporting the data that has been collected. The research results show that the Intellectual Disability Social Service Institution of "Raharjo" Sragen has implemented welfare guarantees for people with disabilities in accordance with applicable laws and regulations. Not only that, the Intellectual Disability Social Service Institution of "Raharjo" Sragen plays an important role in creating independent, skilled and integrated people with disabilities in society. Welfare guarantees for people with disabilities are very important to ensure their rights are fulfilled and they get a decent life. However, in implementing the welfare guarantee policy, there are still obstacles faced, namely social stigmatization, limited facilities, and a lack of human resources, especially social workers.